PEMIKIRAN POLITIK ALI HASJMY - Zulfata Zulfata (Kalam: Jurnal Agama dan Sosial Humaniora, 2017)
The Quran does not explain explicitly about the form of the Islamic State. This reality has created dynamics in view of some Muslim scholars about the concept of an Islamic State. By implication, the Islamic State of discourse continues to escalate the post-war collapse of the caliphate system of Ottoman Turkey (1924 M). The Muslim scholars who actively discuss the concept of the Islamic States were Fazlurrahman, Taha Husayn, Muhammad Natsir, and Ali Hasjmy. This thesis focus on the political thought of Ali Hasjmy, values that are contained in the concept of an Islamic State, according to Ali Hasjmy, and epistemology of Islamic State formation built by Ali Hasjmy. Some of the above problems will be examined by using the integration theory of the Islamic State developed by several Muslim scholars. The integration theory is applied in qualitative research methods with the approach of critical study on some works of Ali Hasjmy. The result of this research found that the style of political thought of Ali Hasjmy is a theological-interconnected meaning Islamic countries contain the value of religious, economic, political and humanitarian. The Islamic State’s epistemology built by Ali Hasjmy are based on principles of Ukhuwah Islamiyah. Ali Hasjmy indirectly confirmed that the existence of the Islamic State has no deadline, so that Islamic countries can only be understood through the mind that is universal. Moreover, the conception of the Islamic State that was initiated by Ali Hasjmy meet elements of epistemology and critical to consider in the process of implementation of Islamic countries at the international level.